Lopinavir-Loaded Self-Nanoemulsifying Drug Delivery System for Enhanced Solubility: Development, Characterisation and Caco-2 Cell Uptake - Khan, Arshad A.; Akhtar, Safia; Yadav, Yogesh; Atiya, Akhtar; Alelwani, Walla; Bannunah, Azzah M.; Mahmood, Syed (Current Drug Delivery, 2023)
Background: The antiretroviral protease inhibitor drug, lopinavir (LPV), is used to treat HIV-1 infection. LPV is known to have limited oral bioavailability, which may be attributed to its poor aqueous solubility, low efficacy and high first-pass metabolism. Self-nanoemulsifying drug delivery systems (SNEDDS) for LPV have been developed and optimised to counter the current issues. Methods: The titration method was used to prepare LPV-loaded SNEDDS (LPV-SNEDDS). Six different pseudo-ternary phase diagrams were constructed to identify the nanoemulsifying region. The developed formulations were chosen in terms of globule size < 100 nm, dispersity ≤ 0.5, dispersibility (Grade A) and% transmittance > 85. Heating-cooling cycle, freeze-thaw cycle, and centrifugation studies were performed to confirm the stability of the developed SNEDDS. Results: The final LPV-SNEDDS (L-14) droplet size was 58.18 ± 0.62 nm, with polydispersity index, zeta potential, and entrapment efficiency (EE%) values of 0.326 ± 0.005, -22.08 ± 1.2 mV, and 98.93 ± 1.18%, respectively. According to high-resolution transmission electron microscopy (HRTEM) analysis, the droplets in the optimised formulation were < 60 nm in size. The selected SNEDDS released nearly 99% of the LPV within 30 min, which was significantly (p < 0.05) higher than the LPV-suspension in methylcellulose (0.5% w/v). It indicates the potential use of SNEDDS to enhance the solubility of LPV, which eventually could help improve the oral bioavailability of LPV. The Caco-2 cellular uptake study showed a significantly (p < 0.05) higher LPV uptake from the SNEEDS (LPV-SNEDDS-L-14) than the free LPV (LPV-suspension). Conclusion: The LPV-SNEDDS could be a potential carrier for LPV oral delivery.
Keywords: titration method